(untitled) (Journal of Foreign Language Studies, 2024)
The study aims at investigating the effectiveness of peer feedback in writing skill at Faculty of English – Vietnam University of Commerce. Through survey questionnaire and the result from pretest and posttest of 62 students, the method proves to be significantly efficient and feasible. Most of the students show positive attitude towards peer feedback and express their willingness to apply this method in other subjects. In this study, the author also puts forth some recommendations for both teachers and students to maximize the effectiveness of peer feedback in order to help Vietnamese students improve their English writing skill and enhance their confidence in the world of work.